2020
DOI: 10.1186/s12916-019-1472-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of smoking cessation pharmacotherapies during pregnancy is not associated with increased risk of adverse pregnancy outcomes: a population-based cohort study

Abstract: Background: Varenicline, bupropion and nicotine replacement therapy (NRT) are three effective pharmacotherapies for smoking cessation, but data about their safety in pregnancy are limited. We assessed the risk of adverse perinatal outcomes and major congenital anomalies associated with the use of these therapies in pregnancy in Australia. Methods: Perinatal data for 1,017,731 deliveries (2004 to 2012) in New South Wales and Western Australia were linked to pharmaceutical dispensing, hospital admission and deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…For these reasons, nicotine replacement therapy has been proposed as advisable for pregnant women who find it hard to stop smoking during pregnancy (Benowitz and Dempsey, 2004). A recent study has shown that nicotine replacement therapy may be relatively protective of the fetus, compared to smoking, for those births that reach full term (Tran et al, 2020). Nevertheless nicotine, which is the major psychoactive component of tobacco smoke and the primary cause of addiction, has been shown to cross the placenta, enter fetal circulation and accumulate in the fetus from as early as 7 weeks of gestation (Jauniaux et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, nicotine replacement therapy has been proposed as advisable for pregnant women who find it hard to stop smoking during pregnancy (Benowitz and Dempsey, 2004). A recent study has shown that nicotine replacement therapy may be relatively protective of the fetus, compared to smoking, for those births that reach full term (Tran et al, 2020). Nevertheless nicotine, which is the major psychoactive component of tobacco smoke and the primary cause of addiction, has been shown to cross the placenta, enter fetal circulation and accumulate in the fetus from as early as 7 weeks of gestation (Jauniaux et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Eleven were conducted in health‐care settings, used routine clinical data [32–42], compared women prescribed or issued NRT with those who were not and were derived from five discrete birth cohorts. A UK cohort reported outcomes in two manuscripts [32,34] and a PhD [38]; a Danish cohort reported outcomes in five papers [33,35,37,39,42] and Canadian [40], US [36] and Australian [41] cohorts were reported in single studies. Eleven studies described NRT administration to small, experimental interventional cohorts of inpatient pregnant women who usually smoked but were temporarily abstinent [43–53], and were based in Sweden [43,48], the United States [45,46,49–53], the United Kingdom [44] and Finland [47].…”
Section: Resultsmentioning
confidence: 99%
“…Maternal age was reported by 17 studies [32–36,38–40,43,45,46,48–53] and used as a confounder in analyses, but not reported in three [33,37,41,42]. Socio‐economic status or education level was reported by 11 studies [32–40,42,51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations